The relationship between self-care and health locus of control in pregnancy: a cross-sectional study of Iranian women - Fatemeh Rezaei; Zahra Zardosht; Yaser Sarikhani; Tahereh Rahimi (BMC Pregnancy and Childbirth)
Abstract Background A pregnant mother's commitment to following medical advice and addressing complications that arise during pregnancy, termed health locus of control (HLC), can significantly impact both maternal and fetal health, resulting in diverse pregnancy outcomes. The objective of this study was to examine the relationship between self-care behaviors in pregnancy and locus of health control. Methods This cross-sectional study focused on 245 pregnant women in Jahrom City during May–August 2024. The samples were selected with a random cluster sampling method. Jahrom was divided into four clusters (including north, south, west, and east), and two health centers were randomly selected in each cluster. The data were collected using the pregnancy self-care and HLC scale. A multivariate logistic regression model was applied to determine the relationship between self-care and HLC by adjusting for age, socioeconomic factors, pregnancy-related factors and place of prenatal care. Results The average age of pregnant women was 30.38 ± 5.96 years. A significant direct correlation was between self-care and the I-HLC (r = 0.35, p < 0.001) and P-HLC (r = 0.25, p < 0.001) dimensions of HLC. After controlling for confounding factors (age, socioeconomic factors, gestational age, planned pregnancy, and place of prenatal care), the odds of increasing self-care in pregnant women with high I-HLC were 1.13 times higher than those with low I-HLC. Also the odds of increasing self-care in pregnant women with high P-HLC were also reported to be 1.11 times higher than those with low P-HLC. Conclusions A positive significant association was reported between P-HLC and I-HLC with self-care behaviors among pregnant women. Thus, one strategy that could assist in diminishing adverse pregnancy outcomes is to reinforce educational programs developed by health planners that emphasize the enhancement of P-HLC and I-HLC in pregnant women.